Pengaruh Model PBL Melalui Pendekatan Diferensiasi Materi Penjumlahan Siswa SD Kelas 1 - Cholifah Tur Rosidah; Rosmiati Rosmiati; Peny Retnasari (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This research aims to determine the effect of the Problem Based Learning learning model through a material differentiation approach on the addition ability of grade 1 elementary school students at SDN Ngagelrejo I/396 Surabaya. The material differentiation approach is carried out by adjusting the level of difficulty of the addition material based on individual student abilities. This research used a quasi-experimental design with two groups, namely an experimental group that received learning using the PBL model and a material differentiation approach, and a control group that received conventional learning. The research subjects were grade 1 students at SDN Ngagelrejo I/396 Surabaya. Data was collected through addition ability tests before and after treatment. The results of the study showed that there was a significant difference between the addition abilities of students in the experimental group and the control group. The PBL model with a material differentiation approach has proven to be effective in improving the addition ability of grade 1 elementary school students at SDN Ngagelrejo I/396 Surabaya. This research recommends the use of the PBL model with a material differentiation approach in mathematics learning in elementary schools, especially at SDN Ngagelrejo I/396 Surabaya.